Tortillera : Poems - Moro-Gronlier, Caridad, 1969- (Book collections on Project MUSE., 2021)
"Tortillera chronicles the life of a Cuban-American daughter, wife and mother as she dismantles the existence she was taught to want in order to evolve into the queer woman she was born to be. Told through intimate, narrative poems, the speaker's life "on the hyphen" is laid bare as she grapples with the effect language, place, and cultural expectations have on sexuality, gender and identity"--